Análise por injeção em batelada com detecção eletroquímica para determinação de diuréticos em formulações farmacêuticas - SILVA, Eduardo Fonseca (2019)
This work aimed to use the BIA injection analysis methodology with electrochemical detection of multiple pulse amperometry (AMP) for determination of furosemide (FRD) and hydrochlorothiazide (HCT) diuretics in pharmaceutical formulations. The determination of these compounds was performed by sequentially applying two potential pulses as a function of time using a 0.04 mol L − 1 Britton-Robinson buffer solution at pH 4.0 as a support electrolyte. FRD was oxidized at +1.10 V, and at +1.30 V there was oxidation of both compounds, and it is necessary to use a correction factor to determine the concentration of HCT. In addition, the measurements showed no surface contamination / passivation of the boron-doped diamond (BDD) working electrode. Under these conditions, after system optimization, the compounds presented linear response range from 2 to 100 μmol L − 1 for HCT (r = 0.9999) and 2 to 300 μmol L − 1 for FRD (r = 0.9993) , good repeatability with DPR less than 5% for n = 30, detection limits of 0.65 μmol L − 1 for FRD and 0.89 μmol L − 1 for HCT, quantitation limits of 1.98 μmol L − 1 for FRD and 1.92 μmol L − 1 for HCT, experimental analytical frequency at 120 injections per hour. The results obtained with the proposed method were compared to those obtained by UV-Vis spectrophotometry, which were statistically similar to a 95% confidence level.